Clinicopathological Features of Ovarian Adult Granulosa Cell Tumor in Dr. Hasan Sadikin General Hospital Bandung from 2019 to 2025 - Ganda Irma Melati; Birgitta M. Dewayani; Etis Primastari (Eduvest - Journal of Universal Studies, 2025)
Adult granulosa cell tumor (AGCT) is the most common ovarian sex cord–stromal tumor (SCST), comprising approximately 70% of cases. It is a low-grade malignant neoplasm with a tendency for late recurrence and metastasis. Tumor stage and rupture in stage I disease are the most important prognostic factors. This study aimed to describe the clinicopathological characteristics of AGCT patients treated at Dr. Hasan Sadikin General Hospital, Bandung, from 2019 to 2025. This observational analytic study included 46 women who underwent surgical resection and were histopathologically diagnosed with AGCT with documented International Federation of Gynecology and Obstetrics (FIGO) stage at Dr. Hasan Sadikin General Hospital between 2019 and 2025. Sampling was consecutive. Variables observed included age, FIGO stage, laterality, ascites, surgical procedures, tumor size, histopathological pattern, mitotic count, necrosis, lymphovascular invasion, endometrial pathology, and adjuvant chemotherapy. Data were analyzed descriptively. The mean age of patients was 47 years (range 19–63). The mean tumor size was 23.7 cm, and most tumors (82.6%) measured ≥10 cm. Nearly all were unilateral (97.8%), with slight predominance in the right ovary (54.3%). Ascites was present in 56.5% of patients. Histologically, 89.1% exhibited multiple admixed growth patterns with low mitotic activity. Necrosis and lymphovascular invasion were observed in 30.4% and 17.4% of cases, respectively. Endometrial alterations were rare (6.5%). Stage distribution was 47.8% stage I, 2.2% stage II, 41.3% stage III, and 8.7% stage IV. Adjuvant chemotherapy was administered to 50% of patients, most frequently paclitaxel–carboplatin (60.8%).